Judicious reduction of supported Ti catalyst enables access to disentangled ultrahigh molecular weight polyethylene - Gote, Ravindra P.; Mandal, Dipa; Patel, Ketan; Chaudhuri, Krishnaroop; Vinod, C. P.; Lele, Ashish K.; Chikkali, Samir H. (Macromolecules, 2018)
Heterogeneous Ziegler-Natta and homogeneous metallocene catalysts are known to produce ultrahigh molecular weight polyethylene (UHMWPE) in the entangled state. On the other hand, only (two) homogeneous single-site catalysts are reported to yield disentangled UHMWPE (dis-UHMWPE). This disparity between the two types of catalysts and the two states of polyethylene can be bridged if a heterogeneous single-site catalyst that can yield dis-UHMWPE is made accessible. Here, one-pot two-step synthesis of a MgCl2 supported [Ti(OEt)(4)] derived catalyst 1 with a two-stage activation strategy is reported to produce dis-UHMWPE. Second activation of catalyst 1 was performed by adding excess modified methylaluminoxane (MMAO12), and XPS analysis indicated that the catalyst existed in only Ti(III) state at [A1]/[Ti] ratio of 600. Catalyst 1 after second activation with MMAO12 was found to be highly active in ethylene polymerization and produced dis-UHMWPE. Polymerization conditions were tailored to obtain molecular weight (M-w) as high as 13 million g/mol PE. To the best of our knowledge, this is the first time a heterogeneous catalyst (catalyst 1) that displays pseudosingle site nature is able to produce dis-UHMWPE. The thus-prepared nascent polyethylene revealed a melting temperature of 141-144 degrees C, which is a characteristic melting transition for a dis-UHMVVPE. The disentangled state of the nascent PE and its M-w and MVVD were further authenticated by rheological investigations. Isothermal time, sweep oscillatory experiments in linear viscoelastic limit revealed a rapid rise in elastic modulus followed by equilibration to plateau modulus, which are characteristic features of the disentangled state. Thus, a pseudo-singlesite heterogeneous catalyst has been accessed, which upon second activation with excess MMAO12 led to the production of dis-UHMWPE.